1898 Ky. Stat. 547 - (:unkn) unknown (My University, 1898)
Sec. 1259: Hunting or fishing on another's land. Any person who shall enter upon the inclosed lands of another for the purpose of shooting, hunting, or fishing, without the consent of the owner or occupant of said lands, shall be fined not less than five nor more than twenty-five dollars.
Keywords: HUNTING REGULATION